Decision Support System for Determining Overtime Employees at PT. Mark Dynamics Indonesia, Tbk with Analytical Hierarchy Process Method - Jamal Mirdad Purba (International Journal of Basic and Applied Science, 2021)
In the company, it is necessary to conduct an assessment in order to provide overtime for employees. How to determine overtime for employees at PT. Mark Dynamics Indonesia is still manual so it is difficult to determine the assessment and determine which employees deserve overtime. This research starts from the stage of analyzing the current system obtained from direct interviews with related parties and observations. While the design method uses the Unified Modeling language (UML) to describe the system design. In this case, the AHP (Analytical Hierarchy Process) method is used to determine the employee overtime. In this case, the decision-making system can provide convenience for PT. Mark Dynamics, Tbk to determine customer employees in improving the quality to determine customer employees who are applied using Microsoft Visual Studio 2010 and Microsoft Access 2010 programming as databases. The system was developed using a software engineering approach, including analysis, design and implementation. At the analysis stage, process analysis, input analysis, output analysis, weakness analysis of the current system and needs analysis are carried out.